2021
DOI: 10.3389/fgene.2021.728476
|View full text |Cite
|
Sign up to set email alerts
|

A Seven-Gene Signature to Predict Prognosis of Patients With Hepatocellular Carcinoma

Abstract: Purpose: Hepatocellular carcinoma (HCC) is one of the most prevalent malignant diseases worldwide and has a poor prognosis. Gene-based prognostic models have been reported to predict the overall survival of patients with HCC. Unfortunately, most of the genes used in earlier prognostic models lack prospective validation and, thus, cannot be used in clinical practice.Methods: Candidate genes were selected from GEPIA (Gene Expression Profiling Interactive Analysis), and their associations with patients’ survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…One study showed that epithelial cell adhesion molecules were downregulated by 5-fluorouracil (5FU) in human HCC cell lines (HepG2, Hep3B and HuH-7) and upregulated by cisplatin in the HuH-7 cells, indicating that these molecules are targets of chemoresistance (51) and play an important role in tumor recurrence and progression. Furthermore, the expression levels of APOA2, RPB4, TTR, APOH and some HCC-related genes were significantly different between HCC and control samples (45,(52)(53)(54). These findings are consistent with the roles played by different stromal cells during tumor growth (55).…”
Section: Discussionsupporting
confidence: 75%
“…One study showed that epithelial cell adhesion molecules were downregulated by 5-fluorouracil (5FU) in human HCC cell lines (HepG2, Hep3B and HuH-7) and upregulated by cisplatin in the HuH-7 cells, indicating that these molecules are targets of chemoresistance (51) and play an important role in tumor recurrence and progression. Furthermore, the expression levels of APOA2, RPB4, TTR, APOH and some HCC-related genes were significantly different between HCC and control samples (45,(52)(53)(54). These findings are consistent with the roles played by different stromal cells during tumor growth (55).…”
Section: Discussionsupporting
confidence: 75%
“…Coincidently, previous studies have reported a close relationship between increased expression of ANXA2 , 31 EGLN3 , 32 GAS2L3 , 33 MKI67 , 31 MMP12 , 34 NQO1 35 and PTTG1 36 genes and poor survival in HCC tumors, while variants of PPP1RB gene have been associated with liver steatosis and increased risk of developing liver cancer 37 . Since our comparison revealed INMT as the most downregulated gene (Supplementary Table S5), we analyzed its expression among the 371 cases from the TCGA database.…”
Section: Resultssupporting
confidence: 52%
“…PLG encodes a serine protease called plasminogen, which is located on the cell surfaces and is essential for the degradation of extracellular matrices, cell migration, inflammation, oncogenesis, and metastasis [30]. PLG was found to be a prognostic protective factor in HCC [31,32] and a potential biomarker for prediction of papillary thyroid carcinoma [33], but there has been no report of it in PDAC. COPS5 (also known as CSN5) is the fifth component of the COP9 signalosome complex and affects a variety of cellular processes [34].…”
Section: Discussionmentioning
confidence: 99%